Pengaruh Locus Of Control (LOC) Dan Kompetensi Terhadap Kinerja Pegawai: Studi Pada Inspektorat Kabupaten Kolaka - Ismanto Ismanto; Niar Astaginy; Nisa Kurnia (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This research aims to determine: (1) The influence of Locus of Control on Employee Performance (Study at the Kolaka Regency Inspectorate). (2) The Influence of Competency on Employee Performance (Study at the Kolaka Regency Inspectorate). This research uses a quantitative method approach. Data collection in this research used observation, documentation and questionnaires. The population of this research is all employees at the Kolaka Regency Inspectorate. Meanwhile, the sample for this research consisted of 48 employees, the sample was determined using census techniques. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on the research results, it is known that the Locus of Control variable has a positive and significant effect on employee performance as indicated by a P-Values value of 0.000. And the Competency variable also has a positive and significant effect on employee performance, this is shown by the P-Values value of 0.037.